2014
DOI: 10.3389/fphar.2014.00199
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporins with anion/monocarboxylate permeability: mechanisms, relevance for pathogen–host interactions

Abstract: Classically, aquaporins are divided based on pore selectivity into water specific, orthodox aquaporins and solute-facilitating aquaglyceroporins, which conduct, e.g., glycerol and urea. However, more aquaporin-passing substrates have been identified over the years, such as the gasses ammonia and carbon dioxide or the water-related hydrogen peroxide. It became apparent that not all aquaporins clearly fit into one of only two subfamilies. Furthermore, certain aquaporins from both major subfamilies have been repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…It has been widely accepted that members of the AQP family, including those from the NIP subfamily, transport noncharged molecules (25,26), although recent studies have suggested that some members of the AQP family could transport charged substrates (27,28). However, the major Al species at low pH (4.2) is the charged Al 3+ ion (29).…”
Section: Nip1;2 Facilitates Passive Bidirectional Aluminum Transport mentioning
confidence: 99%
“…It has been widely accepted that members of the AQP family, including those from the NIP subfamily, transport noncharged molecules (25,26), although recent studies have suggested that some members of the AQP family could transport charged substrates (27,28). However, the major Al species at low pH (4.2) is the charged Al 3+ ion (29).…”
Section: Nip1;2 Facilitates Passive Bidirectional Aluminum Transport mentioning
confidence: 99%
“…an asparagine residue instead of an otherwise perfectly conserved glycine at a helix crossing point, which allows for slippery helix movements that widen the channel permitting passage of partially hydrated anions (12). The situation regarding the protonation state of weak acid substrates, such as organic monocarboxylates, is more complex (13). There are several reports on monocarboxylate permeability of AQPs, mainly for lactate/lactic acid, e.g.…”
mentioning
confidence: 99%
“…Lactate permeation by AQP9 has been previously reported (Tsukaguchi et al 1998; Tsukaguchi et al 1999a). Mechanisms of AQP9 anion transport have been discussed, and AQP9 is proposed to act as a channel for the protonated lactic acid form (Rambow et al 2014). Since humans have a large family of monocarboxylate transporters (MCTs) expressed in all tissues(Halestrap 2013), the physiological role of AQP9 in lactate transport is questionable.…”
Section: Discussionmentioning
confidence: 99%